CREOLIZED TEXT IN MODERN COMMUNICATIVE SPACE: THE ESSENCE OF THE CONCEPT AND PRAGMATICS OF FUNCTIONING - Bovsunivska , Alina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is devoted to the study of creolized text as a phenomenon in the modern communicative space and theoretical approaches to defining the essence of this concept. In defining the concept of «creolized text», the author emphasizes the pluralism of opinions regarding this definition. The article also considers the typological characteristics of the creolized text and pragmatic features of its functioning in improving the efficiency of communication.__________References:• Anisimova, E. E. Lingvistika teksta i mezhkul'turnaya kommunikatsiya (na primere kreolizovannykh tekstov): uchebnoe posobie dlya stud. fak. inostr. yaz. vuzov (Moskva: Tezaurus, 2013), 122.• Voroshilova, M. B. Politicheskiy kreolizovannyy tekst: klyuchi k prochteniyu (Ekaterinburg: Ural'skiy gosudarstvennyy pedagogicheskiy universitet 2013), 194.• Gadoms'ka, A. A. «Metodikamovlennєvo-kul'turnoї adaptatsії іnozemnikhstudentіvzasobamikreolіzovanikhreklamnikhtekstіv» (Dis. kand. fіlol. nauk, Odessa, 2017), 257.• Karpenko, A. V. «Sinesteziyakaksredstvovyrazheniyasimvolistskogomirochuvstvovaniya.» Uchenye zapiski Tavricheskogo natsional'nogo universiteta im. V. I. Vernadskogo. Seriya «Filologiya. Sotsial'nye kommunikatsii» 27 (66), № (2014): 164–170.• Poymanova, V. «Semanticheskoe prostranstvo videoverbal'nogo teksta.» Avtoref. diss. kand. filol. nauk (Moskva, 1997).• Sorokin, A., Tarasov, E. F. «Kreolizovannye teksty i ikh kommunikativnaya funktsiya.» Optimizatsiya rechevogo vozdeystviya (1990): 180-186.
Keywords: creolization, creolized text, verbal component, nonverbal component, communication, communicative space, information and communication technologies, pragmatics